Survivors of the Shoah: Interviewee: Marta Szanto Part II (Survivors of the Shoah Visual History Foundation, 1999)
Shoah Foundation interview code: 49558 Duration: 01:28:00 Interview with Hungarian Holocaust survivor Marta Szanto continued. The tape is part of a collection of 10 interviews provided to OSA by the Survivors of the Shoah Visual History Foundation. Interviewer: Hanna Szemzo.